Shaker collection of records concerning the United Society of Believers in Christ's Second Appearing - Shaker Collection (Library of Congress)
Correspondence, covenants, diaries and journals, financial and legal papers, hymns and hymnals, church orders and instructions, poetry, spiritual communications, inspirational writings and drawings, essays, biographical and historical sketches, memoirs, registers, clippings, and other papers, primarily relating to and emanating from Shaker communities at Enfield, Conn., Pleasant Hill and South Union, Ky., Canaan and New Lebanon, N.Y., and Union Village, Ohio, reflecting many aspects of Shaker belief, life, history, and custom. Includes additional material relating to other communities at Alfred, Me.; Busro (West Union), Ind.; Canterbury and Enfield, N.H.; Hancock, Harvard, Pittsfield, and Tyringham, Mass.; Watervliet, N.Y.; and Watervliet and Whitewater, Ohio. Prominent Shakers represented include Giles Bushnell Avery, David Darrow, Calvin Green, Matthew Houston, Rebecca Jackson, Susanna C. Liddell, Richard McNemar, Joseph Meacham, R.W. Pelham, Seth Y. Wells, and Isaac N. Youngs.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Members of the United Society of Believers in Christ's Second Appearing, a millenial religious sect originating in England among the Society of Friends in the 18th century, were popularly known as Shakers. Ann Lee (1736-1784) brought a small following to New York in 1774; communities were established as far west as Indiana and Kentucky. Mostly farmers and woodworkers, the Shakers were celibate and recruited only by conversion.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Index available in the Library of Congress Manuscript Reading Room.
Keywords: Avery, Giles B. -- 1815-1890.; Darrow, David, -- 1750-1825.; Green, Calvin; Houston, Matthew, -- 1764-1848.; Jackson, Rebecca, -- 1795-1871.; Liddell, Susanna C., -- 1824-; McNemar, Richard, -- 1770-1839.; Meacham, Joseph, -- 1742-1796.; Pelham, R. W. -- 1797-1873.; Wells, Seth Y; Youngs, Isaac N; Shakers -- Connecticut; Shakers -- Indiana; Shakers -- Kentucky; Shakers -- Maine; Shakers -- Massachusetts; Shakers -- New Hampshire; Shakers -- New York (State); Shakers -- Ohio; Alfred (Me.) -- Religious life and customs; Canaan (N.Y.) -- Religious life and customs; Canterbury (N.H.) -- Religious life and customs; Enfield (Conn.) -- Religious life and customs; Enfield (N.H.) -- Religious life and customs; Hancock (Mass.) -- Religious life and customs; Harvard (Mass.) -- Religious life and customs; New Lebanon (N.Y.) -- Religious life and customs; Pittsfield (Mass.) -- Religious life and customs; Pleasant Hill (Ky.) -- Religious life and customs; South Union (Ky.) -- Religious life and customs; Tyringham (Mass.) -- Religious life and customs; Otterbein (Warren County, Ohio) -- Religious life and customs; Watervliet (N.Y.) -- Religious life and customs; Watervliet (Ohio) -- Religious life and customs; West Union (Ind.) -- Religious life and customs; Whitewater (Ohio) -- Religious life and customs